OPERATIONAL MANAGEMENT OF TECHNOLOGICAL COMPLEXES BASED ON THE EVALUATION OF NOISE IMMUNITY OF INFORMATION AND CONTROL SYSTEMS - Temerbekova Barnokhon Maratovna (International Engineering Journal For Research & Development, 2020)
The concept of noise immunity of objects of operational dispatching control of complex technological processes and productions from the point of view of possibility of performance of planned tasks on the basis of an assessment of reliability characteristics of technological knots is entered. It is shown that the application of the fuzzy set theory apparatus to assess the noise immunity of the system under study makes it possible to assess the production situation not only in the presence of objective statistical information about perturbations on the system, but also on the basis of subjective information